Editing with Final Cut Pro 4 : an intermediate guide to uncompressed, DV, and beyond - Roberts, Charles, 1967- (Focal Press, 2004)
The only intermediate Final Cut Pro book on the market that combines editing practices with de-jargonized set up and buyers' guide information.